PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 177 PEKANBARU - Annisa Fitri; Erlisnawati '; Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study was conducted because of low yields V grade students of SD Negeri 177 Pekanbaru. Of the 37 students who achieve KKM only 18 people. The purpose of this research to improve learning outcomes Elementary School fifth grade students 177 Pekanbaru with the implementation of cooperative learning model Numbered Heads Together. The results of the teacher's activities In the first cycle the first meeting of the percentage of activity the teachers 58.3% categorized enough, I sisklus second meeting with a good percentage of 70.8% category. At the first meeting of the second cycle with the percentage of 83.3% is very good category, the second meeting of the second cycle with a percentage of 95.8% is very good category. In the first cycle of the first meeting of the percentage of student activity 54.2% categorized enough, I sisklus second meeting with a good percentage of 62.5% category. The first meeting of the second cycle with the percentage of 79.2% categorized well, the second meeting of the second cycle with a percentage of 91.7% is very good category. Mastery learning students on base score students who completed whereas 18 students who did not complete 19 students with classical completeness 48.64% (not finished). At the end of the first cycle of repeat students who complete 27 people while not complete 10 students with classical completeness 72.97% (not finished) .At the end of the second cycle repetition increased completeness, students who completed 35 students while incomplete 2 students with classical completeness 94.59% (complete.Key Words : Numbered Heads Together, learning outcomes IPS